Modified coconut coir to remove hexavalent chromium from aqueous solution (Bangladesh Journal of Scientific and Industrial Research, 2019)
Hexavalent chromium (Cr(VI)) was removed from aqueous solution by adsorption using chemically modified lignin-rich low-cost coconut coir. The equilibrium time, adsorption isotherm and adsorption kinetics at certain conditions such as pH, particle size and the initial concentration of adsorbate were investigated. The coconut coir was modified by sodium chlorite for adsorption studies. The scanning electron microscopic image depicted the morphology of SCM-CC of different particle sizes whereas the elemental composition of this sort of bioadsorbent was determined by using energy dispersive spectroscopic data. Fourier transform infrared (FTIR) spectrometry analysis indicated that the carbonyl (C=O) groups and hydroxy (O–H) groups from the lignin structure in coconut coir may be involved in the mechanism of Cr(VI) adsorption. The maximum Cr(VI) adsorption capacity of sodium chlorite modified coconut coir (SCM-CC) was found to be 28.03 mg Cr(VI) g-1 SCM-CC at pH 2.00 for the particle size of 75-100 μm with the dose of 7.5 g/L. The equilibrium was established within three hours resulting in the maximum removal (99.92%) of chromium. Freundlich isotherm was better fitted than Langmuir isotherm at pH 2.00 on the basis of the regression coefficient (R2). The kinetic data well-fitted with Ho’s pseudo second order kinetics. The SCM-CC can be treated as an excellent adsorbent for the remediation of chromium toxicity.Bangladesh J. Sci. Ind. Res.54(1), 89-98, 2019